Meta‐Analisis : Gender Dan Depresi Pada Remaja - Nefi Darmayanti (Jurnal Psikologi, 2008)
The purpose of this meta‐analysis study  is  to  evaluate  primary  studies  that  studied gender  differences  in  adolescents  depression. Articles  collected  from  popular  journal  (e.g. journal  of  research,  journal  of  youth adolescent,  American  journal  of  community  psychology,  journal  of  adolescence  and  psychology,  journal  of  adolescence  and journal of abnormal child psychology). Twenty  three  articles  were  found,  but only  fourteen  articles  were  relevant.  After final  evaluation,  only  twelve  articles  with  fourteen studies could be analyzed. Fourteen (14)  studies  involving  5206  subjects examined  gender  differences  in  adolescents depression